Petik Laut as Cultural Resilience: Balancing Tradition and Modern Life in the Coastal Community of Banyuwangi, Indonesia - Clarissa Ayu Fitri Ramadhani; FX Sri Sadewo; Kholida Ulfi Mubaroka (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The Petik Laut tradition in Grajagan Village, Banyuwangi, Indonesia, represents a significant maritime cultural practice that reflects the spiritual connection coastal communities have with the sea. This tradition has been observed since 1977, yet it now confronts challenges posed by modernization and globalization. While scholarly discourse around maritime traditions has increased, there remains a lack of systematic research examining the social reproduction mechanisms that contribute to their continuity. This study seeks to investigate how the meanings and functions of Petik Laut are expressed in the social and spiritual lives of the community. It explores how these communities negotiate traditional values in the face of modern influences and examines the extent to which Petik Laut serves as a mechanism for cultural resilience amid globalization. Utilizing Pierre Bourdieu's social practice theory, this qualitative ethnographic study analyzes the interactions among habitus, capital, and field. Research was conducted in Grajagan Village, Banyuwangi, from September to December, 2024. Data collection involved interviews with ten informants, including traditional leaders, fishermen, village officials, and community members, as well as participant observation and documentation studies. Thematic analysis revealed patterns associated with habitus formation, capital mobilization, and negotiations within the field. The findings indicate that Petik Laut serves as a complex social reproduction mechanism, wherein spiritual habitus interacts with various forms of capital: cultural, economic, social, and symbolic. Specifically, the tradition functions as a spiritual ritual embodying cosmological beliefs, a mechanism for social solidarity through gotong royong (communal cooperation), a source of cultural capital that enhances tourism appeal, and a symbolic arena for negotiating authority and identity. The tradition persists through strategic adaptation, successfully maintaining its spiritual core while embracing digital documentation and engaging younger generations. This study underscores how coastal communities exercise cultural agency within structural constraints, preserving their collective identity through creative adaptation. The findings contribute to the decolonization of social theory and inform culturally sensitive development policies that acknowledge traditional practices as essential foundations for sustainable coastal management.